Burst-Mode Asynchronous Controllers on FPGA. (30th December 2008) - Oliveira, Duarte L.; Strum, Marius; Sato, Sandro S.
Abstract : FPGAs have been mainly used to design synchronous circuits. Asynchronous design on FPGAs is difficult because the resulting circuit may suffer from hazard problems. We propose a method that implements a popular class of asynchronous circuits, known as burst mode, on FPGAs based on look-up table architectures. We present two conditions that, if satisfied, guarantee essential hazard-free implementation on any LUT-based FPGA. By doing that, besides all the intrinsic advantages of asynchronous over synchronous circuits, they also take advantage of the shorter design time and lower cost associated with FPGA designs.